The Implementation of Yandex Engine on Live Translator Application for Bahasa and English Using Block Programming MIT App Inventor Mobile Based - Oktoverano Lengkong, S.Kom., M.Ds.; Green Mandias; Marchel Tombeng (CogITo Smart Journal, 2022)
One of the international languages used today is English. One of the essential things that become the principal capital is the mastery of foreign languages to compete and advance. In communicating, one of the supporting tools used today is a smartphone. They saw the needs and opportunities in terms of communication. The author does research, namely: the use of the Yandex engine, which will be implemented in an Indonesian and English translator application, which is expected to help users to get international language translation results, in terms of vocabulary or vocabulary, as well as pronunciation or how to pronounce/pronunciation words. The research method used is SDLC (Software Development Life Cycle). This method has analysis phases, system design phases, testing phases, and publication phases. This application is built for Android Operating System. The Yandex Engine is used as a translation engine in this research. MIT App Inventor is a tool used to build android-based applications; this tool is a visual programming scratch framework from MIT and implementation of Open Block distributed by the MIT Scheller Teacher Education Program. The result of this research is a mobile-based Indonesian and English Direct Translator engine. MIT App Inventor can work well using the Yandex search engine, which can produce a Live Translator whose features all work correctly and can be said to have the same results as other software development kits.Keywords—Yandex Engine, MIT App Inventor, Visual Programming, Open Block